Oxidation catalysts prepared from biosorbents supported on zeolites - Figueiredo, Hugo (2006)
The catalytic oxidation of 1,2-dichlorobenzene was investigated over NaYand NaX zeolites, loaded with chromiumthrough the action of a robust biosorption system consisting of a bacterial biofilm supported on the zeolites. The results of biosorption showed that the maximum metal removal efficiencywas 20%, in both systems based on NaYorNaX, starting fromsolutions with chromium(VI) concentrations ranging from 50 to 250 mgCr/L. The bacterial biofilm, Arthrobacter viscosus, supported on the zeolite reduces Cr(VI) to Cr(III). The Cr(III) is retained in the zeolite by ion exchange. The new catalysts were characterized by spectroscopic methods (FTIR ), chemical analyses (ICP-AES), surface analysis (XRD) and thermal analysis (TGA). The various techniques of characterization show that this biosorption process does not modify the morphology and structure of the FAUzeolites. These catalysts,Cr/FAU, prepared through this newprocedure present good activity and selectivity for dichlorobenzene oxidation in wet air at 350 ºC. The Cr50-Y was selected as the most active, selective and stable catalyst for oxidation of 1,2-dichlorobenzene in wet air.